The impact of the performance management system (PMS) on service delivery in Mokopane Reginal Hospital Limpopo Province - Chauke, Malose William (University of Limpopo (Turfloop Campus), 2009)
The study investigated the impacts of performance management system on service delivery in Mokopane Regional hospital. The study moved from the premise that Performance Management System in Mokopane Regional Hospitals is not well managed. The investigation however revealed that efforts are being made to implement performance management system although some essential improvements are inevitable required. It also probed the implementation of the performance management system within the ambit of the determined policies and procedure manual for the hospital. The challenges experienced are due to the failure of the line managers and supervisors in understanding the essence of the system. The implementation of the system often results in biasness and other performance unrelated factors. In many instances, other factors (such as subjectivity at the expense of objectivity) are unrelated to high performance rates. The study makes a recommendation on how alignment can be made to ensure that the system become more effective.
Thesis (MPA.) --University of Limpopo, 2009
Keywords: Performance Management System; 658.31250968; Performance standards; Employees -- Rating of